Dynamic surface control for discrete-time strict-feedback systems with network-induced delays using predictive event-triggered strategy. Issue 2 (25th January 2019) - Wu, Ranran; Fan, Ding; Iu, Herbert Ho-Ching; Fernando, Tyrone
ABSTRACT: In this paper, a novel dynamic surface control methodology with a predictive event-triggered strategy is proposed for discrete-time strict-feedback systems. In order to evaluate immeasurable state variables, a least square evaluation method is adopted. A dynamic surface controller is designed for discrete-time strict-feedback systems. When the transmission time of Sensor-to-Controller (S–C) or Controller-to-Actuator (C–A) channel increases, the stability and dynamic performance of the system deteriorates are improved by the proposed predictive event-triggered control strategy. Furthermore, the proposed methodology decreases the use of network resources while the whole system still keeps stable and exhibits an acceptable dynamic performance. The simulation results demonstrate that the proposed methodology is effective.